Double jeopardy - Goldberg, Leonard; Weisberg, David; Cook, Douglas S.; Beresford, Bruce; Paramount Pictures Corporation (Hollywood, California : Paramount Pictures, 2001)
Judd plays Libby Parsons, who discovers that the husband she's convicted of murdering staged his own'death' and framed her for the crime. released on parole, she skips town to find him-and that puts parole officer Travis Lehman (Jones) on her trail
Originally released as motion picture
Includes behind-the-scenes featurette
Director of photography, Peter James ; editor, Mark Warner ; music, Normand Corbeil ; co-producer, Richard Luke Rothschild
Cast : Tommy Lee Jones, Ashley Judd, Bruce Greenwood, Annabeth Gish
Keywords: Revenge -- Drama; Video recordings for the hearing impaired